2004
DOI: 10.1177/0261927x03260809
|View full text |Cite
|
Sign up to set email alerts
|

Different Beliefs

Abstract: This article examines Spanish maintenance in a group of Hispanic teenagers in Sydney. In particular, it looks at the relationship between various attitude clusters and the development/maintenance of various aspects of proficiency. Both open and closed itemswere used, which permitted the emergence of unexpected attitude clusters. The proficiency measures examined a range of aspects of proficiency. Beliefs in favor of bilingualism and a determination to resist the hegemony of the dominant language are significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…For example, some studies (Nelson 2012;Phinney et al 2001) included different subsamples and thus each subsample produced an individual data-set. Some studies (Feuerverger 1989;Gibbons and Ramirez 2004;Kang and Kim 2012;Oh and Au 2005) reported the statistical correlation between the overall ethnic identity and each of the different dimensions of HL proficiency separately, while some studies (Kiang 2008;Maloof, Rubin, and Miller 2006;Oh and Fuligni 2010) reported the correlation between the overall HL proficiency and each of the different dimensions of ethnic identity separately. Hence, each correlation corresponded to an individual data-set.…”
Section: Analysis and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, some studies (Nelson 2012;Phinney et al 2001) included different subsamples and thus each subsample produced an individual data-set. Some studies (Feuerverger 1989;Gibbons and Ramirez 2004;Kang and Kim 2012;Oh and Au 2005) reported the statistical correlation between the overall ethnic identity and each of the different dimensions of HL proficiency separately, while some studies (Kiang 2008;Maloof, Rubin, and Miller 2006;Oh and Fuligni 2010) reported the correlation between the overall HL proficiency and each of the different dimensions of ethnic identity separately. Hence, each correlation corresponded to an individual data-set.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…There is a volume of evidence about this relationship associated with different ethnic groups, including but not limited to Chinese Americans and Chinese Canadians (Feuerverger 1991;Kiang 2008;Noro 2009;Rosenthal and Feldman 1992;Zhang and Slaughter-Defoe 2009;Mehri 2011); Korean Americans and Korean Canadians (Feuerverger 1991;Lee 2002;Hong 2010); Armenian-, Japanese-, Mexican-and Vietnamese-Americans (Chinen and Tucker 2005;Bankston and Zhou 1995;Phinney et al 2001;Maloof, Rubin, and Miller 2006;Imbens-Bailey 1996); Latin-and Asian-Americans (Oh and Au 2005;Oh and Fuligni 2010); Italian-, Portuguese-, Ukrainian-and Jewish-Canadians (Feuerverger 1989(Feuerverger , 1991; Turkish and Hispanic Australians (Yagmur, Bot, and Korzilius 1999;Gibbons and Ramirez 2004); as well as Bangladeshi and Welsh British (Giles and Johnson 1987;Lawson and Sachdev 2004). Studies addressing bi-and multi-ethnic groups are emerging (Mehri 2011;Nelson 2012).…”
Section: Introductionmentioning
confidence: 99%
“…objects of language attitudes are not only language varieties and their speakers but can be as many as all the social and psychological issues connected to the use and the existence of languages. For example, language attitude research includes attitudes towards minority languages (Romaine 1995;Barnes 2009;Gibbons and Ramirez 2004), bilingualism (Baker 1992;Vega 2008), language maintenance and language shift (Bentahila 1983;Hakuta and D'Andrea 1992;Crezee 2012), language variation (Bettoni and Gibbons 1988;Ryan and Giles 1982), codeswitching (Luna and Peracchio 2005;Pauwels 1991), dialects (Liebscher and Dailey-O'Cain 2009) and speech styles (Giles and Powesland 1975).…”
Section: Introductionmentioning
confidence: 99%
“…The children also declared having affective beliefs (Gibbons & Ramírez 2004a) about Colombia and the Spanish language. These positive beliefs towards the ethnic language are positive indicators of future LM (see Holmes et al 1993 whose findings I discussed in Chapter 1).…”
Section: Many Expressions That We Have In Spanish and As Colombians Are Different From What You Say And Feel In English So I Want Them Tomentioning
confidence: 99%
“…Attitudes generally have a cognitive (beliefs), an affective (feelings) and a conative (behavioural) component(Baker 1992:13ff;Garrett 2010). However, past research has used the term belief to refer to both conative and affective components in a manner equivalent to attitude (seeGibbons & Ramírez 2004a;Yu 2010; see also discussion inSallabank 2010:60-63). The term ideology, in contrast, tends to refer to beliefs which are shared by a group of people (seeVan Dijk 2011).…”
mentioning
confidence: 99%